Public service news and social media - Sehl, A; Cornia, A; Nielsen, R (Reuters Institute for the Study of Journalism, 2018)
What strategies do public service media have for news distribution on social media? How do they organise their work? How do they react to changes in the ranking algorithms and products? A new Reuters Institute report looks at how public service news organisations in six European countries (Finland, France, Germany, Italy, Poland and the UK) deliver news via social media at a time when news use is increasingly driven by referrals or consumed off-site on various platforms. The analysis is based on 14 interviews conducted between November 2017 and January 2018, primarily with senior editors and managers for news, or social media for news specifically. We complement the interviews with various analyses of how public service media perform on social media. The social media platforms of our focus are Facebook, Twitter, and Instagram.